Attack, Assent or Defend? Strategic (Political) Responses to Corruption Scandals - Marcelino, Carolina Wünsch; Oliveira, Samir Adamoglu de (Organizações & Sociedade, 2021)
This study aims to identify strategic responses in the official statements issued by the group of political agents mentioned on "Fachin's List". These statements in response to corruption accusations comprise a mediatized corpus of secondary data that was investigated using interpretive discourse analysis. This study uses an institutionalist approach to the political context considering the complexity and plurality of the institutional sphere, in which each voter is an interlocutor of political discourse. This study also included analyses on how the discursive constructions are formed using intertextual, rhetorical, ambiguous and semantic elements. The results outline five distinct strategies in the official notes, which apply both to individuals as well as organizations: (a) attack by expressing consternation; (b) empathy for supporting anti-corruption actions; (c) manipulation by projecting a political ethos; (d) manipulation by revoking legitimacy; and (e) an adaptive posture in raising ambiguity – contributing to reflection and assessment of reactive behaviors of individuals and organizations in situations of crisis, scandals, guiltiness and corruption.